Gender perception on the impact of vocational-technical education on the socio-economic development of Urbanizing Port Harcourt Metropolis, Rivers State, Nigeria - Abali, Temple Probyne; Echeonwu, Charles (Journal of Social, Humanity, and Education, 2022)
Purpose: The study is aimed at determining the impact of vocational-technical education on youths’ socio-economic development. Methodology of Research: Descriptive design was adopted in carrying out the study, with 4 research questions and hypotheses, 6,003 students of the population from the 12 vocational-technical schools in the state, a sample of 400 students, reliability coefficient of 0.72. Mean and standard deviation were used to answer the research questions; z-test was used to test the null hypotheses at a 0.05 Alpha level of significance. Results: The study revealed that vocational-technical education brings about economic development, skill acquisition, employment opportunities, aside from poverty reduction in Port Harcourt Metropolis. The study recommends the provision of infrastructure, adequate funding, and proper implementation of policies in vocational-technical schools in Rivers State, Nigeria. Limitations: This study was limited to the 12 existing public technical-vocational schools in Rivers State, Nigeria. Variables such as skills acquisition, economic development, employment opportunities, and poverty reduction were examined. Contribution: The study will expose the youths to various opportunities and possibilities, helping them to channel their strength and energy to reasonable economic activities. By so doing, social vices will be controlled.